A highly efficient and durable solar evaporator based on hierarchical ion‐selective nanostructures. Issue 2 (18th September 2022) - Li, Lianhui; Du, Lang; Bai, Yuanyuan; Wang, Yongfeng; Hao, Mingming; Liu, Mengyuan; Ge, Changlei; Wang, Shuqi; Zheng, Hui; Li, Lili; Sun, Fuqin; Zhang, Ting
Abstract: Solar‐driven vapor generation technology can directly produce clean water, but existing strategies remain challenging in achieving both high evaporation performance and good salt resistance due to complex water‐thermal management. Here, we constructed hydrogel‐based hierarchically nanostructured evaporator (HNE) with vertically aligned micro water transportation pathways and water confined ion selective nanochannels. Based on the polarity modified hierarchical structures and umbrella‐shaped geometry design, HNEs can achieve high‐speed water transfer at low saturated water content to realize efficient heat energy confinement, and provide more heat exchange sites. Consequently, an exciting water evaporation rate of 3.68 kg m −2 h −1 and the efficiency of 91.1% were achieved under 1 sun solar radiation. More importantly, the overlapping electrical double layer in the narrow nanochannels endows the ions selectivity of the nanochannel to reject anions, resulting in reliable long‐term salt resistance. The ingenious design was creatively confirmed by streaming potential and validated during long‐term efficient work. Abstract : A PSS@PVA@OCB hydrogel‐based hierarchically nanostructured evaporator with vertically aligned micro water transportation pathways and water confined ion‐selective nanochannels is constructed. Based on the fabricated evaporator, an exciting water evaporation rate of 3.68 kg m −2 h −1 and reliable long‐term salt resistance are achieved.